Caracterização e vulnerabilidades dos mananciais urbanos e rurais em relação ao transporte com produtos perigosos na BR - 277, Paraná - Oliveira, Juliana Bento de (2019)
Hazardous Products Road Transport (TRPP) has become a major concern due to the social and environmental problems that can result in an accident, thus causing soil and water contamination, bringing risks to the health of nearby communities and agents which provide services such as: civil defense, firefighters, environmental agents, concessionaire, thus affecting the nearby ecosystem. In this study a survey was carried out on the traffic, classes and accidents involving the transport of dangerous products in the stretch of BR-277, from kilometer (km) 493 to 603 (Guaraniaçu to Foz do Iguaçu), which intercepts three important watersheds state of Paraná, Baixo Iguaçu, Piquiri and Paraná basin, 3 listing the socio-environmental impacts that can cause to sources of supplies located in urban and rural areas. There were registered from the period of 2013 to 2017, 27,501 dangerous cargoes that transited in the stretch. The most transported product classes were flammable liquids, hazardous substances, gases and corrosive substances. Nine accidents with hazardous products were registered in the study section and demonstrated five critical points, that is, where there were more general accidents, being km 584 and 586 (Cascavel) and km 723, 725 and 726 (Foz do Iguaçu). The characterization and environmental fragility of the municipalities of Guaraniaçu and Cascavel were also carried out, because of the eleven municipalities that intercept the stretch of the study, according to the hydrography mapping, these two municipalities are the ones that have the supply sources closest to the BR- 277. For the environmental characterization of municipalities, information on hydrography, economic viability, population estimation, land use and occupation, and climate were used from the National Water Agency (ANA) database, SANEPAR (Companhia de Saneamento do Paraná) , The Brazilian Institute of Geography and Statistics (IBGE), the Paranaense Institute for Economic and Social Development (IPARDES), the Brazilian Forest Service (SFB), the Agronomic Institute of Paraná (IAPAR) and the municipal secretariats of Development and Environment of Cascavel and Guaraniaçu . From the software QGIS version GRASS 7.4.1 the maps of land use and occupation, slope, hypsometry and soil classification were elaborated. The satellite images were used with data from ANA, IBGE and the Brazilian Agricultural Research Corporation (EMBRAPA). In order to use and occupy the ground, we used the Operational Terra Imager (OLI), Scenes 223/77 and 223/78, Landsat-8 satellite, resolution 30 meters, for hypsometry and slope charts, based on SRTM sensor images (MNT data), resolution 30 meters, and for soil classification data Embrapa (2007). From these factors the determination of environmental fragility from the methodology proposed by Ross (1994), Santos et al. (2011), Massa and Ross (2012). Guaraniaçu has 112,748 hectares for agricultural activities, 56% (64,018 ha) are for pasture cultivation, 42.9% of the area of the municipality has a strong undulating slope, referring to hypsometry presented elevations around 800 to 1050 m next to highway, the soil type is a composition of Nitssolo Háplico and Camibissolo Háplico (low permeability), from these characteristics it was possible to determine a high environmental fragility. Cascavel presented that of 176,460 hectares destined to agricultural activities, 57% are destined to permanent and temporary plantations, its slope was classified as 45.2% of the area of the municipality is corrugated, its hypsometry areas higher at 600 to 1050 m of near altitude the highway, and its soil is classified as Red Latosol, Thus the environmental fragility of the municipality from the factors ranged from intermediate to high. Concerning the traffic of dangerous products in the section it is concluded that the area is environmentally fragile and in case of accident with dangerous product, the contamination of the bodies of water and soil will be immediate. Therefore, the study showed the importance of carrying out the diagnosis of the area, and that this is the first step in public health decisionmaking, it should be stressed that preventive and corrective measures in vulnerable regions should be implemented in conjunction with public and private management and the community.